2018
DOI: 10.1155/2018/8406193
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic-Rich Baccaurea angulata Modulates Inflammatory Biomarkers of Atherosclerosis

Abstract: Purpose Cardiovascular disease (CVD) is the leading and the most critical type of chronic disease. Atherosclerosis is the most common cause of CVD. Inflammation has been progressively acknowledged as a vital and central player in the pathophysiology of atherosclerosis. Baccaurea angulata is an underutilized fruit of the island of Borneo. It was obtained from Bau, Sarawak, Malaysia. In our previous studies, B. angulata did not only increase antioxidant enzyme activities, but also slowed the lipid peroxidation p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The As Lee et al [58] indicated, based on the phytochemicals of BNS extract that exhibited hyperlipidemic and hypercholesterolemic activity on fat deposition and lipid profiles, the AI could be improved as the B. nigra sprout extract is clinically functional for treating dyslipidemia. The administration of the plant-based materials reduced the concentrations of induced serum inflammatory biomarkers, and its protective effect against cardiovascular risk might be due to its polyphenol content [61]. These findings were in agreement with our obtained results.…”
Section: Effect Of B Nigra Sprout Extracts On Kidneys' Functions In R...supporting
confidence: 92%
“…The As Lee et al [58] indicated, based on the phytochemicals of BNS extract that exhibited hyperlipidemic and hypercholesterolemic activity on fat deposition and lipid profiles, the AI could be improved as the B. nigra sprout extract is clinically functional for treating dyslipidemia. The administration of the plant-based materials reduced the concentrations of induced serum inflammatory biomarkers, and its protective effect against cardiovascular risk might be due to its polyphenol content [61]. These findings were in agreement with our obtained results.…”
Section: Effect Of B Nigra Sprout Extracts On Kidneys' Functions In R...supporting
confidence: 92%
“…According to the literature, free radicals, oxidative stress, and other genotoxic stressors are the main culprits for most chronic and neurodegenerative diseases, particularly aging ( Ahmed et al, 2015 , Ahmed et al, 2017 , Pisoschi and Negulescu, 2011 , Dzoyem and Eloff, 2015 , El Assar et al, 2013 , Ibrahim et al, 2017 , Ibrahim et al, 2018a , Ibrahim et al, 2018b , Nirmala et al, 2018 ). Furthermore, the associations between ROS generation, inflammation, and disease progression are well established through the stimulation of cytokines release and activation of enzymes (such as lipoxygenases) from the various inflammatory cells ( Dzoyem and Eloff, 2015 , Yin et al, 2016 ).…”
Section: Antioxidants Free Radicals Inflammation and Skincarementioning
confidence: 99%
“…Despite the high-cost implication of managing these inflammatory diseases, the outcomes have not been encouraging because a reductionist approach or a monotherapy model has always been adopted such that a single drug or single bioactive compound is used to attack one target of the disease. The trend now is to explore a group of compounds that are naturally present in foods, known as nutraceuticals or functional foods, for the management of these chronic degenerative diseases, owing to their cheapness, naturalness, safety as well as remarkable preventive and therapeutic potentials ( Ibrahim et al, 2018a , Ibrahim et al, 2018b , Santana-Gálvez et al, 2019 , Aldaddou et al, 2022 , Zamakshshari et al, 2021 , Zamakshshari et al, 2022 ). Our objectives in this review are to critically analyze the setback and limitations of the current anti-inflammatory therapy, the role of free radicals and natural antioxidants in inflammation, the role of inflammation in aging, the potential roles of naturally-derived cosmetics, cosmeceuticals, and nutricosmetics in inflammation-related diseases, the alternatives to common extraction techniques of bioactives vis-à-vis green extraction solvents such as natural deep eutectic solvents and electrochemically reduced water, the enhancement of the bioavailability, stability, solubility, and controlled release profile of the bioactives using different delivery systems as well as the potential global market value, motivators, drivers, trends, challenges, halal and other common certifications for cosmeceuticals and nutricosmetics.…”
Section: Introductionmentioning
confidence: 99%
“…Atherosclerotic diseases are still major causes of mortality globally. B. angulata is claimed to be plaque-reducing activity as a new anti-atherogenic plant which was investigated by using in vivo animal model, where the result showed that treatment with fruit juice of B. angulata reduced plaque formation in rabbits' entire aorta thus decrease serum IL-8 and IL-18 production of inflammatory biomarkers and thus could protect against oxidative stress linked atherosclerosis and decrease the atherogenic index [72][73].…”
Section: Anti-atherosclerotic Effectmentioning
confidence: 99%